Nanoindentation Hardness Distribution and Strain Field and Fracture Evolution in Dissimilar Friction Stir-Welded AA 6061-AA 5A06 Aluminum Alloy Joints - Guangjian Peng; Yi Ma; Jiangjiang Hu; Weifeng Jiang; Yong Huan; Zhitong Chen; Taihua Zhang (Advances in Materials Science and Engineering)
Aluminum alloy AA 6061-T651 and 5A06-H112 rolled plates were successfully welded by friction stir welding (FSW) at three rotation speeds of 600, 900, and 1200 rpm with two transverse speeds of 100 and 150 mm/min. Mechanical properties and strain field evolution of FSW AA 6061-AA 5A06 were characterized by the uniaxial tension and digital image correlation (DIC) tests. Furthermore, the hardness distribution map of whole cross section was obtained via the nanoindentation method with 700 indents. Both DIC and nanoindentation results reveal that the heat-affected zone (HAZ) of AA 6061 alloy is the softest area in the weldment, and the fracture happens in this region. The microstructure evolution characterized by electron-backscatter diffraction (EBSD) indicates that the continuous dynamic recrystallization is the primary grain structure evolution in the stirring zone, and the grain refinement helps improve the mechanical properties. Analyses of the micro- and macrofeatures of the fracture surfaces via scanning electron microscopy (SEM) and optical microscope suggest that the increasing of heat input could enlarge the size of HAZ and reduce the slant angle of HAZ and thus lead the fracture angle to decrease and cause the dimples change from inclined ones to normal ones.